Abnormal pain perception is associated with thalamo-cortico-striatal atrophy in C9orf72 expansion carriers in the GENFI cohort. Issue 12 (5th August 2020) - Convery, Rhian S; Bocchetta, Martina; Greaves, Caroline V; Moore, Katrina M; Cash, David M; Van Swieten, John; Moreno, Fermin; Sánchez-Valle, Raquel; Borroni, Barbara; Laforce Jr, Robert; Masellis, Mario; Tartaglia, Maria Carmela; et al.
Abstract : Objective: Frontotemporal dementia (FTD) is typically associated with changes in behaviour, language and movement. However, recent studies have shown that patients can also develop an abnormal response to pain, either heightened or diminished. We aimed to investigate this symptom in mutation carriers within the Genetic FTD Initiative (GENFI). Methods: Abnormal responsiveness to pain was measured in 462 GENFI participants: 281 mutation carriers and 181 mutation-negative controls. Changes in responsiveness to pain were scored as absent (0), questionable or very mild (0.5), mild (1), moderate (2) or severe (3). Mutation carriers were classified into C9orf72 (104), GRN (128) and MAPT (49) groups, and into presymptomatic and symptomatic stages. An ordinal logistic regression model was used to compare groups, adjusting for age and sex. Voxel-based morphometry was performed to identify neuroanatomical correlates of abnormal pain perception. Results: Altered responsiveness to pain was present to a significantly greater extent in symptomatic C9orf72 expansion carriers than in controls: mean score 0.40 (SD 0.71) vs 0.00 (0.04), reported in 29% vs 1%. No significant differences were seen between the other symptomatic groups and controls, or any of the presymptomatic mutation carriers and controls. Neural correlates of altered pain perception in C9orf72 expansion carriers were the bilateral thalamus and striatum as well as a predominantly right-sided network of regions involving the orbitofrontal cortex, inferomedial temporal lobe and cerebellum. Conclusion: Changes in pain perception are a feature of C9orf72 expansion carriers, likely representing a disruption in somatosensory, homeostatic and semantic processing, underpinned by atrophy in a thalamo-cortico-striatal network.